Enhancing the Conductivity of Cell-Laden Alginate Microfibers With Aqueous Graphene for Neural Applications - McNamara, Marilyn C.; Niaraki-Asli, Amir Ehsan; Guo, Jingshuai; Okuzono, Jasmin; Montazami, Reza; Hashemi, Nicole N. (Frontiers in Materials, 2020)
Microfluidically manufacturing graphene-alginate microfibers create possibilities for encapsulating rat neural cells within conductive 3D tissue scaffolding to enable the creation of real-time 3D sensing arrays with high physiological relavancy. Cells are encapsulated using the biopolymer alginate, which is combined with graphene to create a cell-containing hydrogel with increased electrical conductivity. Resulting novel alginate-graphene microfibers showed a 2.5-fold increase over pure alginate microfibers, but did not show significant differences in size and porosity. Cells encapsulated within the microfibers survive for up to 8 days, and maintain ~20% live cells over that duration. The biocompatible aqueous graphene suspension used in this investigation was obtained via liquid phase exfoliation of pristine graphite, to create a graphene-alginate pre-hydrogel solution.